The History of reading a reader - Towheed, Shafquat 1973-.; Crone, Rosalind; Halsey, Katie (London Routledge, 2011)
Summarises the main debates and perspectives shaping the field of reading. This title introduces key theorists such as Iser, Fish and Bakhtin. It surveys influential works and outlines important studies on mass reading. It focuses on specific communities such as Welsh miners, African American library users and Australian convicts.
Section 1. Defining the field : what is the history of reading? -- Section 2. Theorising the reader -- Section 3. Researching and using literacy -- Section 4. Reading the masses -- Section 5. Reading communities -- Section 6. Individual readers -- Section 7. New directions and methods in the history of reading.
Keywords: Reading -- History; Literacy -- History